The Autophagy in Osteoimmonology: Self-Eating, Maintenance, and Beyond - Xiao, Lan; Xiao, Yin (Frontiers in Endocrinology, 2019)
It has been long realized that the immune and skeletal systems are closely linked. This crosstalk, also known as osteoimmunology, is a primary process required for bone health. For example, the immune system acts as a key regulator in osteoclasts-osteoblasts coupling to maintain the balanced bone remodeling. Osteoimmunology is achieved through many cellular and molecular processes, among which autophagy has recently been found to play an indispensable role. Autophagy is a highly conserved process in eukaryotic cells, by which the cytoplasm components such as dysfunctional organelles are degraded through lysosomes and then returned to the cytosol for reuse. Autophagy is present in all cells at basal levels to maintain homeostasis and to promote cell survival in response to cellular stress conditions such as nutrition deprivation and hypoxia. Autophagy is a required process in immune cell activation/polarization and osteoclast differentiation, which protecting cells from oxidative stress. The essential of autophagy in osteogenesis is its involvement in osteoblast differentiation and mineralization, especially the role of autophagosome in extracellular calcium transportation. The modulatory feature of autophagy in both immune and skeleton systems suggests its crucial roles in osteoimmunology. Furthermore, autophagy also participates in the maintenance of bone marrow hematopoietic stem cell niche. The focus of this review is to highlight the role of autophagy in the immune-skeleton interactions and the effects on bone physiology, as well as the future application in translational research.